2015
DOI: 10.1155/2015/928534
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Variability and Implications of Meteorological Dry/Wet Conditions in the Poyang Lake Catchment, China, during the Period 1960–2010

Abstract: This paper presents a quantitative investigation of the variability of meteorological dry/wet conditions of the Poyang Lake catchment during 1960-2010 by using the standardized precipitation-evapotranspiration index (SPEI) based on daily observations of 14 meteorological stations across the catchment. Extending from previous studies, the background of the encounter and overlap of multitimescales of meteorological dry/wet episodes for several severe drought and flood events were discussed. In addition, the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
2
16
1
2
Order By: Relevance
“…For wet episode calculated from SPEI_pm and SPEI_th, the most frequent occurrence was in winter, varying from 18% to 20%, and the second-highest frequency occurred in spring with the same frequency of 18.8%. The results here generally concur with Ye et al [53]. Ye et al showed that the most frequent occurrence of wet episode was in November, December, and February.…”
Section: Spatial Variationsupporting
confidence: 93%
“…For wet episode calculated from SPEI_pm and SPEI_th, the most frequent occurrence was in winter, varying from 18% to 20%, and the second-highest frequency occurred in spring with the same frequency of 18.8%. The results here generally concur with Ye et al [53]. Ye et al showed that the most frequent occurrence of wet episode was in November, December, and February.…”
Section: Spatial Variationsupporting
confidence: 93%
“…The basin contains five main subbasins: the Ganjiang, Fuhe, Xinjiang, Raohe, and Xiushui River Basins (Figure 2). Poyang Lake (115°49′-116°46′ E, 28°24′-29°46′ N), which is China's largest freshwater lake, mainly receives water from these five rivers before discharging into the Yangtze River at Hukou [19]. The topography in the Poyang Lake Basin is quite complex, which consists of mountainous areas, subordinate hills, and alluvial plains.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…However, the SPI only considers the influence of precipitation. In the context of global change, rising temperature has become one of the important factors aggravating drought processes [19]. Therefore, the objective characterization of drought conditions requires us to consider the joint effects of precipitation and temperature changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the SPEI, which is calculated as the difference between precipitation and potential evapotranspiration (PET), is used to describe the severity of drought conditions [26,37,38]. e ornthwaite and Penman-Monteith approaches are widely applied in the calculation of PET [39,40].…”
Section: Standardized Precipitation Evapotranspiration Indexmentioning
confidence: 99%